Signaling pathways in cutaneous wound healing - Krizanova, Olga; Penesova, Adela; Sokol, Jozef; Hokynkova, Alica; Samadian, Amir; Babula, Petr (Frontiers in physiology, 2022)
Wound healing is a very complex process, where variety of different pathways is activated, depending on the phase of healing. Improper or interrupted healing might result in development of chronic wounds. Therefore, novel approaches based on detailed knowledge of signalling pathways that are activated during acute or chronic cutaneous wound healing enables quicker and more effective healing. This review outlined new possibilities of cutaneous wound healing by modulation of some signalling molecules, e.g., gasotransmitters, or calcium. Special focus is given to gasotransmitters, since these bioactive signalling molecules that can freely diffuse into the cell and exert antioxidative effects. Calcium is an important booster of immune system and it can significantly contribute to healing process. Special interest is given to chronic wounds caused by diabetes mellitus and overcoming problems with the inflammation.
Keywords: hydrogen peroxide; diabetes mellitus; calcium; wound healing; gasotransmitters